Hypoxia Up-Regulates Galectin-3 in Mammary Tumor Progression and Metastasis - de Oliveira, Joana T. (PLoS One, 2015)
The tumor microenvironment encompasses several stressful conditions for cancer cells such as hypoxia, oxidative stress and pH alterations. Galectin-3, a well-studied member of the beta-galactoside-binding animal family of lectins has been implicated in multiple steps of metastasis as cell-cell and cell-ECM adhesion, promotion of angiogenesis, cell proliferation and resistance to apoptosis. However, both its aberrantly up- and down-regulated expression was observed in several types of cancer. Thus, the mechanisms that regulate galectin-3 expression in neoplastic settings are not clear. In order to demonstrate the putative role of hypoxia in regulating galectin-3 expression in canine mammary tumors (CMT), in vitro and in vivo studies were performed. In malignant CMT cells, hypoxia was observed to induce expression of galectin-3, a phenomenon that was almost completely prevented by catalase treatment of CMT-U27 cells. Increased galectin-3 expression was confirmed at the mRNA level. Under hypoxic conditions the expression of galectin-3 shifts from a predominant nuclear location to cytoplasmic and membrane expressions. In in vivo studies, galectin-3 was overexpressed in hypoxic areas of primary tumors and well-established metastases. Tumor hypoxia thus up-regulates the expression of galectin-3, which may in turn increase tumor aggressiveness.